Linear Polymer Cathode Materials for Highly Efficient Aqueous Zinc‐Ion Batteries: Is the High Active Sites Density Necessary? - Yiyang Dai; Yao Yao; Liang Feng; Zhenglong Qiu; Min Deng; Qiang Peng (Advanced Science, 2025)
Abstract Recently, research on aqueous zinc‐ion batteries (AZIBs) has always focused on improving the energy storage performance by increasing the number of active sites, particularly in designing organic/polymer materials with a high density of active sites. However, does a higher density of active sites necessarily induce enhanced energy storage performance? To verify this issue, we have designed two linear polymers, where TAPT‐DHBQ contains an additional pair of active sites (carbonyl groups) compared to TABQ‐DHBQ, with theoretical specific capacities of 545.26 and 379.14 mAh g−1, respectively. Interestingly, the experimental results have deviated with the specific capacities of these polymers being comparable, measuring to be 325 mAh g−1 (TABQ‐DHBQ) and 280 mAh g−1 (TAPT‐DHBQ). This is attributed to the competition effect between neighboring active sites, which leads to decreased utilization of active sites. As a result, the Zn//TABQ‐DHBQ batteries with ZnI2 electrolyte additive have exhibited high specific capacities of 618 and 360 mAh g−1 at the current densities of 1 and 10 A g−1, along with a high energy density of 678.6 Wh kg−1 (1 A g−1). The finding underscores the importance of uniform electron cloud distribution in cathode materials for achieving efficient AZIBs.